2022
DOI: 10.1111/jpi.12823
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates PM2.5‐induced glucose metabolism disorder and lipidome alteration by regulating endoplasmic reticulum stress

Abstract: Exposure to fine particulate matter (PM 2.5 ) was associated with an increased incidence of liver metabolic disease. Melatonin has been shown to prevent liver glucolipid metabolism disorders. However, whether melatonin could rescue PM 2.5 -induced liver metabolic abnormalities remains uncertain. This study was to evaluate the mitigating effect of melatonin on PM 2.5 -accelerated hepatic glucose metabolism imbalance in vivo and in vitro. Schiff periodic acid shiff staining and other results showed that PM 2.5 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Accumulating evidence from work in animal and cellular models is supportive of the mechanistic framework that air pollutant exposure can alter miRNAs, thereby impacting liver fat and/or systemic lipid metabolism ( Ding et al, 2019a ; Du et al, 2022b , 2022a ; Zhu et al, 2022 ). Additional work in mouse models has demonstrated that PM 2.5 -induced hepatic steatosis and dyslipidemia may be driven by altered expression of gene pathways regulating oxidative stress and lipid metabolism ( Ding et al, 2019b ; Wang et al, 2020 ; Xu et al, 2019 ; Zheng et al, 2013 ).…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence from work in animal and cellular models is supportive of the mechanistic framework that air pollutant exposure can alter miRNAs, thereby impacting liver fat and/or systemic lipid metabolism ( Ding et al, 2019a ; Du et al, 2022b , 2022a ; Zhu et al, 2022 ). Additional work in mouse models has demonstrated that PM 2.5 -induced hepatic steatosis and dyslipidemia may be driven by altered expression of gene pathways regulating oxidative stress and lipid metabolism ( Ding et al, 2019b ; Wang et al, 2020 ; Xu et al, 2019 ; Zheng et al, 2013 ).…”
Section: Discussionmentioning
confidence: 97%
“…We found out that OPTN overexpression significantly upregulated the expression FLNA, which was associated with the inhibition of ERS in DCM. Moreover, GSK3β and FoxO1 participate in the occurrence and development of DCM through ERS and glycophagy (Divari et al, 2020; Du et al, 2022; Wu, Lu, et al, 2023; Wu, Xu, et al, 2023). The beneficial effect of OPTN on DCM is likely through regulation of the GSK3β/FoxO1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…UPM exposure disturbs lipid metabolism in the liver, 72 , 73 lung, 74 and even the cardiovascular system, 75 resulting in SREBP-1 activation, abnormal serum cholesterol levels, and lipid accumulation. 76 , 77 The quality and synthesis of meibum, an important actor secreted by the MG, were significantly impaired in UPM-exposed populations.…”
Section: Discussionmentioning
confidence: 99%